2018
DOI: 10.26434/chemrxiv.7454420.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variable-Temperature Multinuclear Solid-State NMR Study of Oxide Ion Dynamics in Fluorite-Type Bismuth Vanadate and Phosphate Solid Electrolytes

Abstract: <p>In this study, we employ a multinuclear, variable-temperature NMR spectroscopy approach to characterise and measure oxide ionic motion in the V- and P-substituted bismuth oxide materials Bi0.913V0.087O1.587, Bi0.852V0.148O1.648 and Bi0.852P0.148O1.648, previously shown to have excellent ionic conduction properties. Two main <sup>17</sup>O NMR resonances are distinguished for each material, corresponding to O in the Bi–O and V–O/P–O sublattices. Using variable-temperature (VT) measurements … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…These values are in excellent agreement with NMR data for motions in the V−O (0.06 ± 0.02 eV) and P−O (0.04 ± 0.02 eV) sublattices, 31 as well as with the small activation barriers of 0.05−0.07 eV previously reported for other tetrahedral species like MnO 4 − and SO 4 2− . 32,33 We, therefore, conclude that the dynamics we observe on IN5 are localized motions of O atoms within the VO x and PO 4 polyhedra; similar flexibility of the VO x polyhedra has also been reported for Sr-doped BiVO 4 .…”
Section: Nanosecond Dynamics In Bvo-148 and Bpo-148supporting
confidence: 91%
See 1 more Smart Citation
“…These values are in excellent agreement with NMR data for motions in the V−O (0.06 ± 0.02 eV) and P−O (0.04 ± 0.02 eV) sublattices, 31 as well as with the small activation barriers of 0.05−0.07 eV previously reported for other tetrahedral species like MnO 4 − and SO 4 2− . 32,33 We, therefore, conclude that the dynamics we observe on IN5 are localized motions of O atoms within the VO x and PO 4 polyhedra; similar flexibility of the VO x polyhedra has also been reported for Sr-doped BiVO 4 .…”
Section: Nanosecond Dynamics In Bvo-148 and Bpo-148supporting
confidence: 91%
“…The activation energy found for BVO-148 is in good agreement with that of 0.16 ± 0.02 eV found by 17 O T1 relaxation measurements from solid-state NMR for dynamics in the Bi− O sublattice, which the authors ascribed to nearest neighbor vacancy jumps. 31 Despite impedance data showing significant ionic conductivity for BVO-148 in the measured temperature range, 14 this long-range diffusion is likely too slow to fall completely within the timescale probed by IN16b, meaning that the nanosecond dynamics observed in this study on BVO-148 and BPO-148 are predominantly local nearest neighbor jumps.…”
Section: Nanosecond Dynamics In Bvo-148 and Bpo-148mentioning
confidence: 66%
“…significant localised or delocalised disorder of ions between O2 and O3 sites) and ionic conductivity in Ba3M2O8.5±δ-type conductors is clear, as has been recognised in other oxide ion conductors. 9,[30][31] Some insight into the causal relationship between relatively high O3 occupancy and superior ionic conductivity in these materials can be gained by considering the O 2positional energy landscape, which is well approximated using easily-calculated BVEL maps. 23 Fop et al showed that a curved minimum-energy O 2conduction pathway (valley) connects nearest-neighbouring O2 sites via a saddle point near O3, and noted a correlation between the activation energy barrier at this saddle point and refined O2/O3 occupancies among a series of Ba3(Nb,V)MoO8.5 conductors and Ba3NbWO8.5.…”
mentioning
confidence: 99%
“…Although non-trivial due to the complexity and size of the simulation model and the trajectories needed, such computational studies are possible and, especially when interpreted in conjunction with experimental methods, they can provide qualitative and quantitative insight into oxide ion dynamics in structurally complex materials. [30][31][32][33][34][35][36][37]…”
mentioning
confidence: 99%
“…Owing to the special coordination effects, 3D open framework, and electrochemical stability, some phosphates salts have been widely used as electrolytes. 13,14 Moreover, adopting phosphate-based polyanions as SIBs and PIBs anodes would possess the following advantages: (1) rapid ion transfer to improve rate performance; (2) strong coordination effect to increase capacity; (3) 3D open framework and stable structure give rise to the durability. 1,15,16 More specifically, TiP 2 O 7 displays superior electrochemical performance in aqueous SIBs and PIBs.…”
mentioning
confidence: 99%